Nondipping in Parkinson's Disease - Sita Sommer; Billur Aral-Becher; Wolfgang Jost (Parkinson's Disease)
Objective. The aim of this study was to identify patients with Parkinson's disease who showed loss or decrease of nocturnal blood pressure fall (nondipper patients) as a marker of autonomic dysfunction. Presence or absence of orthostatic hypotension was considered to investigate whether alterations in circadian blood pressure pattern are associated with posture-related dysregulation of blood pressure. Methods. 40 patients with Parkinson's disease underwent 24-hour blood pressure monitoring. 21 patients were diagnosed with arterial hypertension and received anti-hypertensive drugs. Nondipper patients were defined as having nocturnal decrease of mean systolic and diastolic blood pressure less than 10%. Presence or absence of orthostatic hypotension was determined by Schellong's test. Results. We identified 35 nondipper patients (88%). Nondipping was detected in 20 patients with orthostatic hypotension (95%) and in 15 patients without orthostatic hypotension (79%). 18 patients with hypertensive and 22 patients with normal blood pressure values were detected. Conclusions. In conclusion 24-hour blood pressure monitoring showed a high prevalence of nondipping in 40 patients with Parkinson's disease with and without orthostatic hypotension independent of coexisting arterial hypertension and antihypertensive treatment. 24-hour blood pressure monitoring may be useful to identify non-dipping as a marker of autonomic dysfunction in patients with Parkinson's disease.